(untitled) (Bodhi Path, 2024)
As Siddhartha, son of Suddhodana, the chief of the Sākya Republic, the Buddha was born and raised in Kapilvatthu. His mother Maha̅ma̅ya gave birth to him in a grove at Lumbini while she was travelling from kapilavatthu to her parents’ home and died after seven days after the birth of Siddhartha. The story goes that soon after he was born, an old sage named Asita visited King Suddhodhana’s palace to see the newborn child. It is said that "on seeing the marks of greatness on its delicate limbs, Asita laughed and shed tears of sorrow" These marks can be related to the 32 marks of a Mahapurusa. According to the Buddhist tradition, a maha̅purusa can be of two kinds – "A World Conqueror or World Renouncer." But King Suddhodana wanted his son to be an Emperor. He did not want his son to turn his back on the world and hence took great pains to shield him from its sorrows and protect the young prince from worldly suffering. So he brought him up in a highly artificial atmosphere, with three palaces to suit the three seasons, surrounded by luxury and pleasant things. Siddhartha married Yashodhara, and they were blessed with a son named Rahula. The hagiography tells us that when Siddhartha was 29 years old, he saw four things that completely shattered his composure – An old man, a diseased man, a corpse and an ascetic". The first three scenes brought home to him the harsh realities and inevitabilities of old age, sickness and death. The fourth pointed out the way of dealing with these inevitabilities. Siddhartha left his home and family; he tore himself away from everyone and rode towards the forest. He wandered in his quest for knowledge for six years, seeking the truth. Siddhartha attached himself to teachers, such as Alāra Kalāma and Udraka Ra̅maputra, but was not satisfied by their instruction. Accompanied by five wandering ascetics (Assaji, Mahānāma, Vappa, Bhaddiya and Kondanna), he also practised severe austerities with the belief that the mind became elevated by emaciating the body until he was reduced to a skeleton. However, at the end of six years, he then realized that he must nourish his body and try to attain peace of mind by partaking in food again. His companions misread his intentions and abandoned him, thinking he had compromised his asterism. The Siddhartha ultimately attained Buddhahood and became known as the Buddha, the enlightened one or the awakened one. Here, it is essential to note that the significance is laid so much on the Enlightenment because it is what made Gautama, the Buddha when he discovered the law of causation or pattica samuppa̅da, which is a cycle of twelve causes and effects conditioning the universe which had not been thought before by anyone. The Buddha opens the discourse by advising the monks to avoid the two extremes of sensual indulgence and self-mortification as follows: These two extremes, O Bhikkhus, should not be followed by one who has left home to live a homeless life. What are these two extremes? • The giving up to the pleasures of sense, which is base, vulgar, wordy, ignoble and profitless. • Giving up on self-mortification is painful, ignoble, and profitless. In the King of Samādhi Sutra, the Buddha said: Existence and non-existence are extremes, Purity and impurity are extremes as well, Thus, having relinquished both extremes, The wise do not dwell even in the middle. The Nāgārjuna explained: To say "it is" is a conception of permanence, To say "it is not" is a view of nihilism, Therefore, the learned should dwell In neither existence nor non-existence.